The Nature of Scientific Justification: W. V. O. Quine’s Coherentism - Imam Wahyudi; Rachmanda Aquila Arkhano; Gladwin Panjaitan (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2026)
W.V.O Quine is an American analytic philosopher of naturalism. His naturalist view tendstowards scientific positivism and empiricism. In the mid-20th century, he criticized the views of logical positivism, which he thought were less radical. In linewith his views, Quine has an epistemological style that aligns with scientific reasoning. This alignment is shown by his coherentist justification theory, which is described as a web of beliefs. Coherentism as a justification assumes that beliefs are interconnected. Thus, if a belief is justified, it will justify other beliefs. Through this coherentism, Quine's holistic view that brings together the unity of analytic and synthetic constructions in language can be realized. Coherentism is the opposite of foundationalism, which holds that justification requires a basic belief as a foundation. This paper aims to explain the style of justification and the history of Quine's scientific philosophy. This paper also aims to explain the implications of W.V.O. Quine's coherentism in the history of philosophy. This paper presents notes on some disagreements with his Coherentist view. The argumentation of this paper is that Quine’s scientific coherentism still needs criteria of consistency.